Opportunistic microorganisms in patients undergoing antibiotic therapy for pulmonary tuberculosis - Querido, Silvia Maria Rodrigues [UNESP]; Back Brito, Graziella Nuernberg [UNESP]; Santos, Silvana Soléo Ferreira dos; Leão, Mariella Vieira Pereira; Koga-Ito, Cristiane Yumi [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP] (Sociedade Brasileira de Microbiologia, 2011)
Antimicrobial therapy may cause changes in the resident oral microbiota, with the increase of opportunistic pathogens. The aim of this study was to compare the prevalence of Candida, Staphylococcus, Pseudomonas and Enterobacteriaceae in the oral cavity of fifty patients undergoing antibiotic therapy for pulmonary tuberculosis and systemically healthy controls. Oral rinsing and subgingival samples were obtained, plated in Sabouraud dextrose agar with chloramphenicol, mannitol agar and MacConkey agar, and incubated for 48 h at 37ºC. Candida spp. and coagulase-positive staphylococci were identified by phenotypic tests, C. dubliniensis, by multiplex PCR, and coagulase-negative staphylococci, Enterobacteriaceae and Pseudomonas spp., by the API systems. The number of Candida spp. was significantly higher in tuberculosis patients, and C. albicans was the most prevalent specie. No significant differences in the prevalence of other microorganisms were observed. In conclusion, the antimicrobial therapy for pulmonary tuberculosis induced significant increase only in the amounts of Candida spp.
Keywords: tuberculosis; Candida; Enterobacteriaceae; Pseudomonas spp; Staphylococcus